2021
DOI: 10.1088/1361-6587/abf253
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of autoresonant stimulated Raman scattering in transversely weakly magnetized plasmas

Abstract: We investigate the behaviour of backward stimulated Raman scattering (BSRS) in inhomogeneous plasma with a transverse external magnetic field via 1D and 2D particle-in-cell simulations and theoretical analysis. The external magnetic field B e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Eventually the particle detraps after accelerating to the escape speed and then continues executing cyclotron motion in p x -p y space. [19] In addition, the forward SRS is slightly enhanced in the external magnetic field, as shown in Fig. 5(b1).…”
Section: Simultaneous Suppression Of Sbs and Srs By The Alternating F...mentioning
confidence: 82%
See 3 more Smart Citations
“…Eventually the particle detraps after accelerating to the escape speed and then continues executing cyclotron motion in p x -p y space. [19] In addition, the forward SRS is slightly enhanced in the external magnetic field, as shown in Fig. 5(b1).…”
Section: Simultaneous Suppression Of Sbs and Srs By The Alternating F...mentioning
confidence: 82%
“…5 is B z = 60 T, the electron cyclotron frequency ω c = 1.96 × 10 −3 ω 0 (ω c /ω 0 1) and the influence of an external magnetic field on the dispersion relations of electromagnetic waves and EPWs is negligible. [19] The spectrum signal of SRS with B z = 0 T is shown in Fig. 5(a1).…”
Section: Simultaneous Suppression Of Sbs and Srs By The Alternating F...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the longitudinal magnetic field makes hot electrons move along the magnetic lines of force, which reduces the growth rate of Weibel instability [25][26][27]. Many works [28,29] have indicated that the kinetic BSRS can be suppressed when the magnetic field (≳20 T) is perpendicular to the laser propagation direction. Since the amplitude of EPW is suppressed and the BSRS is suppressed accordingly, the Weibel instability will no longer be important.…”
Section: Introductionmentioning
confidence: 99%